A Look Back: Teacher unions, quality, and professionalism, as seen in Kappan. (March 2020) - Preston, Teresa
The nature of the teaching profession has been a frequent topic in Phi Delta Kappan. Teresa Preston reviews what Kappan authors have written about the meaning of professionalism in teaching, how teacher unions and collective bargaining have contributed to perceptions of the profession, and how teacher quality has been defined .